PENGARUH MATA KULIAH PLP 2, PERSEPSI PROFESI GURU, DAN LINGKUNGAN KELUARGA TERHADAP MINAT MENJADI GURU PADA MAHASISWA PENDIDIKAN BISNIS DAN PENDIDIKAN ADMINISTRASI PERKANTORAN STAMBUK 2020 UNIVERSITAS NEGERI MEDAN - Ardila, Syifa Milliana; Putra, Pasca Dwi (Fakultas Ekonomi Universitas Negeri Medan, 2024)
This study aims to determine the influence of the PLP 2 course, perceptions of the teaching profession, and family environment on the interest in becoming a teacher among Business Education and Office Administration Education students of the 2020 cohort at Universitas Negeri Medan. This research is quantitative in nature. The population consists of 148 students. The sampling technique used is Random Sampling. The data collection technique employed is a questionnaire. The data analysis technique used is multiple linear regression with hypothesis testing, namely, the Partial Test (t-test), Simultaneous Test (F-test), and Coefficient of Determination. Based on the data analysis conducted, the results show that both simultaneously and partially, the PLP 2 course, perceptions of the teaching profession, and family environment have a significant influence on the interest in becoming a teacher. Keywords: PLP 2, Perception of the Teaching Profession, Family Environment, and Interest in Becoming a Teacher.